Conference on Lasers and Electro-Optics 2019
DOI: 10.1364/cleo_qels.2019.ff1d.2
|View full text |Cite
|
Sign up to set email alerts
|

Heteronuclear Soliton Molecules in Optical Microresonators

Abstract: Optical soliton molecules are bound states of solitons that arise from the balance between attractive and repulsive effects. Having been observed in systems ranging from optical fibers to mode-locked lasers, they provide insights into the fundamental interactions between solitons and the underlying dynamics of the nonlinear systems. Here, we enter the multistability regime of a Kerr microresonator to generate superpositions of distinct soliton states that are pumped at the same optical resonance, and report th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…1(c)]. One should note that this bichromatically driven multistability is physically distinct from the multistability regime driven in a single resonance by a modulated laser [41], as the modulated light source in the earlier work could not create soliton lattice traps with intracavity potential wells. In contrast, here the solitons are continuously drifting over the minima and maxima of the lattice traps, yet they are able to survive.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations
“…1(c)]. One should note that this bichromatically driven multistability is physically distinct from the multistability regime driven in a single resonance by a modulated laser [41], as the modulated light source in the earlier work could not create soliton lattice traps with intracavity potential wells. In contrast, here the solitons are continuously drifting over the minima and maxima of the lattice traps, yet they are able to survive.…”
Section: Introductionmentioning
confidence: 81%
“…In this work, by simultaneously pumping two optical resonances in the same mode family of a microresonator, we demonstrate that each resonance can be independently driven to its upper or lower stable branch of Kerr bistability [37,38]. As a result, the system can be operated in the regime of multistability, where multiple stable equilibrium states are allowed [39][40][41][42]. This bichromatically pumped multistability allows us to deterministically generate soliton collisions as well as composite solitons [see Fig.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…This implies that, while several CSs can simultaneously coexist [18,34], all of them are expected to exhibit identical characteristics. Recent studies have shown [35,36], however, that this expectation can fail when two (or more) fields with different frequencies drive the resonator: each driving field can then sustain CSs with distinct characteristics. In particular, researchers have used polychromatic driving fields to achieve coexistence between CSs associated with different spatial or polarization mode families of a microresonator [35], achieving compact sources of dual-and even triple-combs.…”
mentioning
confidence: 99%